Perencanaan Keuangan dalam Meningkatkan Kedisiplinan Siswa Melalui Program Ketarunaan - Frebi Setia Pringga; Devi Octavianty; Suharyanto H. Soro; Ida Tejawiani (Civiliza Publishing, Indonesia., 2026)
Vocational education is faced with the challenge of equipping graduates not only with technical skills, but also with a strong disciplined character. This study aims to find and analyze school financial planning in supporting the success of improving student discipline through the Cadet Program. This study uses qualitative research with a case study approach. Data collection methods are carried out through observation, in-depth interviews, and documentation studies with informants including the Principal, Treasurer, Cadet Coordinator, and students. The results of the study indicate that (1) Financial planning is carried out systematically through the School Activity and Budget Plan Application (ARKAS) with pure funding sources from Regular School Operational Assistance (BOS); (2) The use of funds is focused on honorariums for external instructors (TNI/Koramil). The conclusion of this study is that systematic financial planning can improve student discipline, punctuality, and responsibility.